Variables Affecting Complication Rates in Type III Paediatric Supracondylar Humerus Fractures. (December 2021) - Livermore, Andrew T.; Sansone, Jason M.; Machurick, Maxwell; Whiting, Paul; Hetzel, Scott B.; Noonan, Kenneth J.
Purpose: Unstable supracondylar humerus (SCH) fractures may have different outcomes as a result of direction of displacement and pin configuration. This study evaluates the impact of fracture displacement, pin configuration and fellowship training on clinical and radiographic outcomes in unstable fractures. Methods: A total of 99 patients with completely displaced type III fractures were identified at an academic centre and a local community hospital. Patient characteristics and the fellowship training of the treating surgeon were recorded, and injury films documented the direction of displacement. Pin configuration, coronal and sagittal alignment were recorded from postoperative radiographs and at healing. Radiographic outcomes including coronal, sagittal and rotational malunion as well as clinical complications were analyzed. Results: Fractures with direct posterior displacement had a lower composite malunion rate compared with those with posterolateral (PL) or posteromedial (PM) displacement (6.9%, 36.4%, 29.2% respectively; p = 0.019). PM displacement had a higher rate of coronal malunion compared with PL (18.2% versus 0%; post hoc p = 0.024). All-lateral constructs resulted in more rotational malunions (20.9% versus 1.8%; p = 0.002) compared with crossed pinning. PL fractures treated with all-lateral fixation showed a trend toward increased rotational instability or malunion (23.8% versus 1.3%; p = 0.073). Higher composite complication rates were noted in patients treated by surgeons with non-paediatric, non-trauma fellowship training. Conclusion: For displaced SCH fractures, all-lateral fixation is associated with higher rates of rotational instability and malunion. Posteromedially and posterolaterally displaced fractures have higher rates of malunion compared with fractures with straight posterior displacement. Fellowship training other than paediatric or trauma was associated with increased complications. Level of Evidence: Level III